Giardiasis in Endoscopy Patients: A Comparison of Diagnostic Techniques. (1st February 1990) - Watson, Doone R; Sutherland, Lloyd; Befus, A Dean
Abstract : The results of a study comparing techniques for diagnosis of giardiasis during endoscopy are presented. Methods of diagnosis included examination of duodenal biopsy impression smears, culture of both biopsies and aspirates, and examination of preserved aspirate. Giardiasis was diagnosed in three of 80 patients; in each case the impression smear was positive. Cultures of duodenal biopsies were positive in two patients; in the third patient a biopsy was not available. The preserved aspirate was positive in only one patient, while the aspirate cultures were never positive. It is proposed that during diagnostic endoscopy, routine submission of a duodenal biopsy impression smear from patients with unexplained small bowel diarrhea or abdominal discomfort is appropriate.